2022
DOI: 10.1161/strokeaha.121.037419
|View full text |Cite
|
Sign up to set email alerts
|

Biological Age Acceleration Is Lower in Women With Ischemic Stroke Compared to Men

Abstract: Background: Stroke onset in women occurs later in life compared with men. The underlying mechanisms of these differences have not been established. Epigenetic clocks, based on DNA methylation (DNAm) profiles, are the most accurate biological age estimate. Epigenetic age acceleration (EAA) measures indicate whether an individual is biologically younger or older than expected. Our aim was to analyze whether sexual dichotomy at age of stroke onset is conditioned by EAA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The reduction in species richness correlates with a worse outcome after IS in both human and animal models [30,31], possibly due to the decrease in the relative abundance of common core bacteria [30]. This is in agreement with the fact that women have a less favourable outcome after stroke than men [4]. We also found increased levels of Fusobacteria, Fusobacteriia, Proteobacteria and Verrucomicrobia, Fusobacteria are part of the dominant phyla of the gut microbiota [33].…”
Section: Discussionsupporting
confidence: 85%
“…The reduction in species richness correlates with a worse outcome after IS in both human and animal models [30,31], possibly due to the decrease in the relative abundance of common core bacteria [30]. This is in agreement with the fact that women have a less favourable outcome after stroke than men [4]. We also found increased levels of Fusobacteria, Fusobacteriia, Proteobacteria and Verrucomicrobia, Fusobacteria are part of the dominant phyla of the gut microbiota [33].…”
Section: Discussionsupporting
confidence: 85%
“…[49][50][51] Furthermore, additional profiling studies showed that biological age (DNAm age), which is measured by circulating levels 5mC, can predict stroke risk, outcome, and recurrence more accurately than chronological age. [52][53][54][55][56] Thus, these studies collectively indicate that blood levels of methylated DNA may serve as a biomarker for the diagnosis, prognosis and treatment of stroke.…”
Section: Stroke and Dna Methylationmentioning
confidence: 92%
“…In particular, both DNAm age and methylation of SLC6A4 hold promise as biomarkers for stroke risk, recurrence, and outcome. [46][47][48][52][53][54][55][56] The current evidence indicates that epigenetic modulators have tremendous potential as biomarkers for both injury and response to therapy.…”
Section: Epigenetic Regulators As Therapeutic Targets In Strokementioning
confidence: 99%
“…The DNAm age of IS patients is higher than their chronological age and that for matched controls [ 169 ]. DNAm age is also a better predictor of IS mortality [ 170 ]. More recently DNAm age differences between men and women, at the time of stroke onset, have been reported [ 170 ].…”
Section: Future Omics Studies In Stroke Researchmentioning
confidence: 99%
“…DNAm age is also a better predictor of IS mortality [ 170 ]. More recently DNAm age differences between men and women, at the time of stroke onset, have been reported [ 170 ].…”
Section: Future Omics Studies In Stroke Researchmentioning
confidence: 99%